1998
DOI: 10.1002/j.1941-2452.1998.tb03059.x
|View full text |Cite
|
Sign up to set email alerts
|

Total Parenteral Nutrition During Pregnancy in a Patient Requiring Long‐Term Nutrition Support

Abstract: Patients on long-term TPN can conceive successfully and carry a pregnancy to term without any adverse outcome for the mother or the fetus. TPN feeding during pregnancy and recommendations for maternal weight gain are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In a systematic literature review, we identified 14 publications describing 15 cases of parenteral nutrition from preconception to delivery in 14 women dependent on long‐term HPN 7 20 . Here, we additionally report the case of a 26‐year‐old Caucasian woman with SBS secondary to recurrent thromboembolic mesenteric infarctions receiving both HPN and high‐dose dual anticoagulation throughout pregnancy and beyond.…”
mentioning
confidence: 99%
“…In a systematic literature review, we identified 14 publications describing 15 cases of parenteral nutrition from preconception to delivery in 14 women dependent on long‐term HPN 7 20 . Here, we additionally report the case of a 26‐year‐old Caucasian woman with SBS secondary to recurrent thromboembolic mesenteric infarctions receiving both HPN and high‐dose dual anticoagulation throughout pregnancy and beyond.…”
mentioning
confidence: 99%